Qualitative enquiry on the perceptions related to MCQ based discussion through WhatsApp status among medical students and teaching faculty during COVID-19 lockdown - Doddaiah, Sunil Kumar; Kulkarni, Praveen; Mohandas, Aparna; M.R, Narayana Murthy (International Journal Of Community Medicine And Public Health, 2021)
Background: Ever since the government of India announced countrywide lockdown, medical institutions across the country has shifted to virtual learning. Being in an era of smartphone users, the utility of a popular social media platform like WhatsApp in efficient learning needs to be explored. The aim of the study was to determine the perceptions related to multiple choice question (MCQ) discussion through WhatsApp status among medical students and teaching faculty. Methods: This longitudinal study was conducted among 154 participants (medical students and faculty) for three months. MCQs on COVID-19 were disseminated through WhatsApp status of the investigator and feedback regarding the same was taken at the end of three months. The qualitative data collected as descriptions were compiled and analyzed as per classical content analysis. Specific codes were assigned to responses and were put under different categories with similar characteristics. Results: A total of 154 participants took part in the study. Participants felt that the approach to convert a popular social media like WhatsApp to a learning platform was innovative. According to them, the activity motivated them to learn more and kept them updated on COVID-19. A major advantage of WhatsApp based learning, being that it can be used anytime and anywhere, which is relevant in the lockdown period. Conclusions: In this study, participants found learning via WhatsApp to be interesting and motivating. Learning through this platform helped the participants to keep themselves engaged in the academics in spite of lockdown and also provided opportunity to clarify their doubts.